An evaluation of the National Health Insurance scheme in the light of South Africa’s constitutional and international law obligations imposed by the right to health - Du Toit, Michelle (Stellenbosch : Stellenbosch University, 2017)
Thesis (LLM)--Stellenbosch University, 2017.